Perilaku Perjalanan pada Akhir Pekan oleh Rumah Tangga yang Tinggal di Daerah Pinggiran Kota Semarang - Ulfa, Ikfi Maryama; Suwandono, Djoko (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2014)
Nowadays the activity of the population in the metropolitan cities on weekend have started to increase the impact on the serious congestion in city center where the entertainment facilities placed. Due to the inequality of facilities resulted by urban sprawl, residents in rural areas become a potential trip generation towards the central bussiness district (CBD) in accessing entertainment and recreation needs on weekend. These problems, can be more complicated due to an increase in welfare, population growth, and an increase in private vehicle ownership. Therefore, the necessary understanding of weekend travel behavior as a way to build a proper transport policy. This study uses a quantitative approach with frequency distribution and multiple linear regression as analysis tools to find the factors of spatial and non-spatial households that affect travel behavior. The study shows that households that live closer to the CBD will be encouraged to increase the travel frequency to meet social needs, recreation, and entertainment on weekend, while staying far away from the CBD will increase their travel distance. The trip will be varied in line with the changes in social conditions, demographic, and economic ownership of household such as children under 16 years of age, car ownership, increased revenue and expenditure entertainment by household.